The Cycle of Violence: Understanding Individual Participation in Collective Violence. (February 2015) - Littman, Rebecca; Paluck, Elizabeth Levy
Abstract : Why do "ordinary" people engage in collective violence, harming others on behalf of their group? In this article, we argue that the violent group itself, and the identity it bestows on participating members, is an often overlooked and yet fundamental source of motivation for an individual's participation in collective violence. Reviewing insights from social and moral psychology, military history, and public health, we outline how the psychology of individual violent behavior presents a puzzle. For an ordinary person, participation in violence is often an aversive and distressing experience, and yet violent behavior leads to more violence in the future. A better understanding of the dynamics of collective violence allows us to make sense of this paradox. Violent groups can promote violent behavior among members by increasing members' motivation to engage in violence, particularly through group identification and deliberate strategies, and by removing psychological obstacles to violence (i.e., by making violence less aversive). Our synthesis of the literature points to a cycle of individuals' participation in collective violence, in which group identification motivates violent behavior and violent behavior increases identification with violent groups.